Decoding CBCT of Inverted Impacted Mesiodens for its intervention and Surgical Considerations: A Case Report - Pokhrel, Srija; Limbu, Senchhema; Singh, Sumit; Dikshit, Parajeeta; Malla, Manisha; Tripathi, Roshila (Journal of Nepalese Association of Pediatric Dentistry, 2024)
Impacted mesiodens in an inverted position near the nasal cavity, pose unique challenges due to their anatomical proximity to critical surrounding structures. Confirmatory diagnosis, radiographic approach and surgical management of such mesiodens is crucial for minimizing post operative complications. Timely intervention prevents aesthetic and occlusal complications such as crowding, displacement of tooth, root resorption and cyst formation thereby preserving both functional and cosmetic outcomes for the patient.This case report showcases two conical supernumerary teeth, erupted one diagnosed as Conical vertical mesiodens and the other as Conical vertical impacted mesiodens subgroup class 5 based on its position within maxilla after Cone Beam Computed Tomography (CBCT) review and Mupparapu’s classification of mesiodens. An indepth analysis with CBCT for thorough planning for surgical management of the impacted and inverted mesiodens has been emphasized in this report. It also highlights the critical considerations that must be addressed both preoperatively and intraoperatively to minimize potential complications.